2011
DOI: 10.1007/s10344-011-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, nutritional status and season on the reproductive system in wild male mink (Neovison vison)

Abstract: The objectives of this study on the reproductive system of wild male mink (Neovison vison) were to determine the influence of age, nutritional status and season on reproductive traits and to produce baseline data that may be used in environmental monitoring programmes. The 117 male mink included in the study were killed by hunters all over Sweden (from latitude 56°N to 67°N) during August to the end of April from 2005 to 2008. The weights of penis, testes, and epididymides were lower, the anogenital distance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…To our knowledge, this is the first time that year-round spleen weight measurements have been presented for a wild carnivore species. A study on wild male American mink Neovison vison (Persson et al 2011) and a report focusing on wild boar Sus scrofa (Fernández-Llario et al 2004) showed that animal spleens were heaviest during winter, but these studies only compared data from 3 and 2 seasons, respectively. Two hypotheses are offered in previous studies to explain seasonal variation in indicators of immunity in vertebrates (Martin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time that year-round spleen weight measurements have been presented for a wild carnivore species. A study on wild male American mink Neovison vison (Persson et al 2011) and a report focusing on wild boar Sus scrofa (Fernández-Llario et al 2004) showed that animal spleens were heaviest during winter, but these studies only compared data from 3 and 2 seasons, respectively. Two hypotheses are offered in previous studies to explain seasonal variation in indicators of immunity in vertebrates (Martin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the mink were born the 1st of May, they were categorized into three age groups; juvenile (3–12 months old, n = 56), one year old (13–24 months, n = 48) and two or more years old (older than 24 months n = 18). According to hours of day length on capture date and site, the mink were divided into seasonal groups (spring, summer, autumn and winter), as previously described [ 29 ]. Upon necropsy, body weight was recorded and the mink were inspected for gross lesions and the internal organs were dissected and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…For examining the influence of this variable on the body condition and the relative spleen, liver, kidney and adrenal weight (% of body mass), the general linear model (GLM) procedure of SAS was used. As organ weights and body condition may be influenced by other factors such as sampling season, age, sex and the weight of the subcutaneous fat [ 29 ], these factors were also tested and included in the models when significant. When needed, the dependent data were log-transformed to improve normality of the residuals.…”
Section: Methodsmentioning
confidence: 99%
“…Metal concentration was used as an independent variable. Dependent variables were sampling season (categorical; winter, spring, summer, autumn, according to previous studies [24]), age (continuous, 0-4 yr old), body condition (continuous; the weight of the subcutaneous fat pad between the hind legs [grams] divided by body weight [kilograms]), and area (categorical; 6 areas, see the section Sampling and postmortem procedure). Interactions between the dependent variables were tested but found to be insignificant (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%